2019
DOI: 10.1177/1178636119890302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Influenza in Season 2017/2018 in a German Emergency Department: A Retrospective Analysis

Abstract: Introduction: Influenza infection is a viral disease with significant morbidity and mortality during the cold months. Clinical presentation typically includes cough, fever, and pain. Influenza disease is hardly diagnosed only on the basis of clinical symptoms due to similar clinical presentation of other diseases such as a typical cold or other flu-like diseases. We evaluated patients with proven influenza who presented at an emergency department of internal medicine in a university hospital according to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The in-hospital mortality in this group of patients was significantly higher (22.4%) than that in those who did not require admission to an ICU. Our observed in-hospital mortality rate of 6.7% was comparable to the in-hospital mortality rate of 5.8% reported by another German university hospital [5] but lower than the in-hospital mortality (8.3%) rate reported by a tertiary hospital in Austria [6]. Interestingly, the in-hospital mortality observed in this season was significantly lower compared to the in-hospital mortality in the 2014/2015 season (7.0% vs. 10.4%) in study hospital No.…”
Section: Discussionsupporting
confidence: 86%
“…The in-hospital mortality in this group of patients was significantly higher (22.4%) than that in those who did not require admission to an ICU. Our observed in-hospital mortality rate of 6.7% was comparable to the in-hospital mortality rate of 5.8% reported by another German university hospital [5] but lower than the in-hospital mortality (8.3%) rate reported by a tertiary hospital in Austria [6]. Interestingly, the in-hospital mortality observed in this season was significantly lower compared to the in-hospital mortality in the 2014/2015 season (7.0% vs. 10.4%) in study hospital No.…”
Section: Discussionsupporting
confidence: 86%
“…Adults shed influenza virus for an average of one week with a peak on the second day of the illness, whereas shedding cessation in children can be prolonged with a noticeable decline in RNA detection in the samples collected in the subsequent days [ 27 , 64 , 65 ]. A study in Germany showed that the mean duration of symptoms before admission to the emergency department was 5.2 days and did not differ significantly between influenza A and B [ 66 ]. Similarly, a study in China estimated the duration from onset of symptoms to hospitalization for IAV patients to be 5.9 days; although it was longer than that for influenza B patients (3.7 days).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalized pandemic H1N1 patients in our analysis appear to have higher frequencies of fever, fatigue, vomiting, shortness of breath and diarrhea compared with hospitalized seasonal influenza patients ( Zhang et al, 2020 ). However, comorbidities including diabetes, COPD, immunocompromised status and heart disease seem more common in seasonal influenza patients compared with pandemic H1N1 patients ( Mohammad et al, 2019 ). Nevertheless, future studies are required to comprehensively, for example by systematic review and meta-analysis, compare COVID-19 with pandemic and seasonal influenza.…”
Section: Discussionmentioning
confidence: 99%